1993
DOI: 10.1002/ijc.2910530427
|View full text |Cite
|
Sign up to set email alerts
|

Expression of autocrine motility factor receptor in serum‐ and protein‐independent fibrosarcoma cells: Implications for autonomy in tumor‐cell motility and metastasis

Abstract: The motile response of serum-dependent (Gc-4 SD) and protein-independent (Gc-4 PF) murine fibrosarcoma cells to monoclonal antibody (MAb) that binds to gp78 a cell-surface receptor (M(r) 78,000) for an autocrine motility factor (AMF) was analyzed. The Gc-4 PF cells responded to the anti-gp78 by increased motility in vitro (3-fold) and increased lung colonization in vivo (8- to 20-fold), while the serum-dependent counterpart failed to respond to motile stimulation both in vitro and in vivo. Immuno-analysis of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…The expression of gp78 was found in Gc-4 PF cells as described previously, 18 and was augmented by transfection with Adamf/phi in a dose-dependent manner (Figure 4a). In contrast, no expression of gp78 was observed in DPF cells even in the cells transfected by amf/phi gene at 100 MOI (Figure 4b), suggesting absence of the receptor for AMF in DPF cells.…”
Section: Adenovirus-mediated Intracellular and Extracellular Expressisupporting
confidence: 78%
See 2 more Smart Citations
“…The expression of gp78 was found in Gc-4 PF cells as described previously, 18 and was augmented by transfection with Adamf/phi in a dose-dependent manner (Figure 4a). In contrast, no expression of gp78 was observed in DPF cells even in the cells transfected by amf/phi gene at 100 MOI (Figure 4b), suggesting absence of the receptor for AMF in DPF cells.…”
Section: Adenovirus-mediated Intracellular and Extracellular Expressisupporting
confidence: 78%
“…One was a murine fibrosarcoma cell line, Gunma clone-4 protein-free (Gc-4 PF), 5 in which the motility and metastatic capacity show high responses to AMF by increased expression of the receptor. 18 Another was Dunn osteosarcoma protein free (DPF), a mouse osteosarcoma cell line. 33 Gc-4 PF cells were cultured in RPMI 1640 medium without serum.…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metastatic dissemination of tumor cells to secondary sites requires highly motile cancer cell behavior which appears to be influenced by growth factors, cytokines, and other molecules yet to be identified [2,3]. We and others have demonstrated that 3T3-CM, which is used as a chemoattractant in the Matrigel invasion chamber assay, contains a number of motility factors that increase the invasiveness of breast cancer cells [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The motile behavior of tumor cells appears to be regulated, in part, by growth factors and cytokines [2,3]. Stromal tissue surrounding the tumor cells produces growth factors which are known to enhance tumor cell proliferation and progression to a metastatic phenotype [4].…”
Section: Introductionmentioning
confidence: 99%